1999
DOI: 10.1001/jama.281.11.991
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Pharmacological Therapies for Late-Life Insomnia

Abstract: LEEP DISTURBANCE IS A PREVAlent problem in late life. Between 12% and 25% of healthy seniors report chronic insomnia, and these estimates are even higher among older adults with coexisting medical or psychiatric illness. 1-4 In addition to normal age-related changes in the physiological aspects of sleep, the increased incidence of health problems and medication use, combined with lifestyle changes associated with retirement, place older adults at increased risk for disrupted sleep. 5 Insomnia, the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
566
2
21

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 987 publications
(602 citation statements)
references
References 30 publications
13
566
2
21
Order By: Relevance
“…Both the safety and the effectiveness of sleeping pills for treatment of insomnia in chronic older adult insomniacs are questionable (Endeshaw 2001;Morin et al 1991;Ray et al 2000). Daytime carryover effects observed with longeracting sleep medications (Johnson and Chernik 1982) are likely to produce additional, potentially serious, decrements in daytime function among chronic older adult insomniacs.…”
Section: Discussionmentioning
confidence: 99%
“…Both the safety and the effectiveness of sleeping pills for treatment of insomnia in chronic older adult insomniacs are questionable (Endeshaw 2001;Morin et al 1991;Ray et al 2000). Daytime carryover effects observed with longeracting sleep medications (Johnson and Chernik 1982) are likely to produce additional, potentially serious, decrements in daytime function among chronic older adult insomniacs.…”
Section: Discussionmentioning
confidence: 99%
“…CBTI is considered first-line treatment for chronic insomnia and can be successfully utilized in patients with mTBI [100][101][102][103][104][105]. Previous reports have shown that CBTI reduced daytime fatigue and improved nocturnal sleep quality among patients with TBI [48].…”
Section: Insomnia and Circadian Dysregulationmentioning
confidence: 99%
“…The effects of pharmacotherapy were essentially limited to the period during which patients were taking the drug. 18 Use of a mind-body intervention can be combined with pharmacotherapy in the treatment of insomnia. Studies examining the relative advantages of CBT and pharmacotherapy have found that improvements may be achieved more quickly with drug treatment; however, improvements are more sustained with CBT.…”
Section: Introductionmentioning
confidence: 99%